The Effect of Kegel Exercises on Female Stress Urinary Incontinence Outcome - El-Deeb, Hoda Abdou Abd El-Monem; Ahmed, Rasha Fathy (International Journal For Research In Health Sciences And Nursing, 2020)
Abstract: Stress urinary incontinence (SUI) is the involuntary leakage of urine on exertion struggle, sneezing, or coughing” by the International Continence Society, is the foremost common sort of urinary incontinence in women. In spite of the fact that it isn't a life-threatening condition, SUI affects women’s social and personal relationships, as well as limiting physical activity. Conservative treatment is now acclaimed as first-line treatment in women with mild and moderate symptoms. Conservative treatments, a nonsurgical treatment, include Kegel exercises which are the most prevalent strategy of strengthening pelvic floor muscles and are noninvasive treatment .They are the most cost-effective treatment. The aim of this study was to explore the effect of kegel exercises on female stress urinary incontinence outcome. Methods: sixty patients with SUI were selected and randomly divided into study group and control group. Patients in the study group received kegel exercises, while those in the control group didn’t receive any intervention. Follow-up was continued for 3 months after intervention. Results: the study revealed that there was significant effects on the study group related to the effect of kegels’ exercise training on female urinary incontinence patients’ signs and symptoms including decreasing urine leaking while coughing, sneezing, bending down, bracing something up walks hastily, shaking or exercise, decreasing urine running down legs onto floor, decrease using pads and expand sexual life. Also there was a significant influence on the study group patients’ daily activities, physical activities, social activities and emotional wellbeing. Conclusion: Kegel exercises for female SUI patients have significant improvement in outcome criteria of urinary incontinence.